Relationship between QRS duration on Admission ECG and Angiographic Severity of Coronary Artery Disease in Patients with Acute Anterior Myocardial Infarction - Rahman, Md Ataur; Ullah, Mohammad; Hossain, Md Iqbal; Ali, Md Bonday; Kader Akanda, Md Abdul (Cardiovascular Journal, 2022)
Background: Early risk stratification of patients with myocardial infarction is critical to determine optimum treatment strategies and improve outcomes. This study was designed to determine the relation between QRS duration on admission ECG and severity of coronary artery disease (CAD) in patients with acute anterior myocardial infarction (AMI). Methods: This observational study was carried out from November 2019 to October 2020 with total of 100 patients with first attack of anterior MI who were treated with thrombolytic therapy. Based on the cut-off value of QRS duration 100, the patients were divided into two groups – one group with QRS duration £100 msec (normal QRS) and another group with QRS duration > 100 msec (prolonged QRS). Severity of CAD was assessed using Gensini score derived from coronary angiographic data. Gensini score < 36 points was regarded as mild coronary artery disease and Gensini score ³36 points as moderate to severe coronary artery disease. Then patients with prolonged and normal QRS durations were compared with severity of CAD to find their association. Results: Acute AMI patients with prolonged QRS duration (> 100 msec) more often tend to be associated with severe CAD. Risk of having severe CAD in patients with prolonged QRS duration were almost 8 (95% of CI = 3.2– 19.3) times higher than those with normal QRS duration (£100 msec) (p < 0.001). Conclusion: The study concluded that three out of four patients of acute anterior MI with prolonged QRS duration are likely to have severe CAD. QRS duration more than 100 msec can be used as a cheap, easily available prognostic factor in patients with acute anterior MI. Cardiovasc j 2022; 14(2): 143-149